Restoration of postbreakdown gate oxide by white-light illumination - Kawashima, Tomohito (2018)
From conductive-atomic-force-microscope probe measurement, we show that electrical conduction through a nanoscale percolation path in the MOSFET gate oxide can be disrupted, either completely or partially, by white-light illumination. This phenomenon is consistently observed in the SiO2 and HfO2 gate-oxide materials, and thus is believed to have originated from a common mechanism-light-stimulated oxygen migration and recombination with vacancy sites that constitute the percolation path. The finding points to the prospect of reliability rejuvenation by the light-assisted restoration of postelectrical-breakdown gate oxides, as well as light-enabled memory operation based on logic MOSFET devices.